Applied English for academic and professional purposes : for senior high school - Tandoc, Shiella D. (Manila : Mindshapers Co., Inc., 2016)
"This book is designed to cater the needs of the learner for improvement of writing skills in essays, research, and technical reports. Writing exercises are provided to give ample practice for the learner to demonstrate his/her skills. Texts across disciplines are provided to give the learner proper exposure to authentic texts".
Includes references.
English text
Keywords: English language--Rhetoric--Handbooks, manuals, etc; Academic writing--Handbooks, manuals, etc; Report writing--Handbooks, manuals, etc